Assessment Of Pattern, Practice And Wastage Of Medicine-Use Among Undergraduate Students Of Universiti Sains Malaysia - Verma, Ashutosh Kumar (2018)
Medicines are boon when used responsibly but irresponsible uses are cause for concern. Another health risk is associated with inappropriate drug use. This irrational practice often associated with risk on health and economic burden. The increase in the cost of drugs is also linked to factors such as irrational drug use and consumer behavioural aspects that lead to wastage. Majority of drug wastage is due to sub-consumption of medicine when consumers do not finish the medications prescribed by their doctors. In Malaysia as reported by National Survey on Use of Medicine (2012 and 2015), more than half of the population does not understand the proper use of medicine where a large proportion is young and studying.